Assessment of groundwater contamination and the risks associated with these uses in an urban microbasin in Campina Grande-PB (Research, Society and Development, 2021)
This work aimed to evaluate the contamination of groundwater in two urban micro- basins in Campina Grande-PB, emphasizing the risk associated with the use of these waters. Data were collected from February to August 2017. During this period, points of contamination in the study area were identified and a questionnaire was applied to assess the uses of groundwater. Physical-chemical and microbiological indicators were also analyzed to assess the quality of these waters. According to the results, there were points of contamination near the wells and the predominant use identified was cleaning environments, however 1% ingested this water. The data obtained indicated that there was contamination by chloride, fluoride, E. Coli and total coliforms, being unsuitable for human ingestion. If these waters are ingested, users will be subject to the risk of contracting diseases such as dental and skeletal fluorosis, as well as complications such as high blood pressure and kidney stones.